Oral aphthous ulcers associated with orlistat - Sheikh-Taha, Marwan (2016)
Orlistat, a reversible inhibitor of gastrointestinal lipase, is indicated for obesity management including weight loss and weight maintenance when used in conjunction with a reduced-calorie diet. It is also indicated to reduce the risk of weight gain after prior weight loss. At the recommended dosage of 120 mg three times daily, orlistat inhibits dietary fat absorption by approximately 30%. The drug should be given with meals or up to one hour after each meal.1 The most common adverse effects reported in patients receiving orlistat are gastrointestinal symptoms, including abdominal discomfort, oily spotting, flatus, fecal urgency, fatty or oily stools, increased defecation, and fecal incontinence. Rare but serious adverse effects include liver failure and oxalate nephropathy.1,2 We report two cases of oral aphthous ulcers associated with the use of orlistat. In the first...